Researching the Impact of the Updated Securities Law on Listed Companies' M&A Performance - Wang, Zheyu (International Journal of Global Economics and Management, 2024)
Based on the empirical analysis of the M&A events of A-share listed companies from 2010 to 2023, this paper explores the impact of the implementation of the new securities law on the M&A performance of listed companies. The findings indicate that the enforcement of the novel securities law has markedly enhanced the M&A efficacy of listed entities, primarily by boosting the transparency of information dissemination, refining the agency dynamics, and elevating market efficiency. The reliability and consistency of this conclusion are verified by descriptive statistics, multiple regression analysis and robustness test. Based on the research conclusions, this paper puts forward some policy suggestions, such as further improving the securities law, improving the information disclosure requirements, optimizing the regulatory environment of capital market, and encouraging the merger and reorganization of enterprises.